Pengembangan Sistem Deteksi Memakai Masker Menggunakan Open CV, Tensorflow dan Keras - Johanes Christianto Tiku; Wahyu Andi Saputra; Novian Adi Prasetyo (JURIKOM (Jurnal Riset Komputer), 2022)
In 2020 the country had contracted the covid 19 virus. The very significant spread made the government have to issue regulations regarding the implementation of health protocols for wearing mask to inhibit the development of the covid 19 virus in the community in real time. By utilizing technological developments in the field of deeplearning and computer vision, this study aims to detect maskon people's faces based on the classification made in the system of wearing maskand not wearing memakai maskers. This study used tensorflow/hard, opencv and deeplearning to perform classification and detection on faces. Based on the results of the confusion matrix test using 100 test data with a group of 50 wearing maskand 50 not wearing memakai maskers, it resulted in 91% Accuracy to detect maskon the faceTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//